THE PROBLEMS OF REALIA IN LITERARY TRANSLATION - Abdumajit Mamadaliev (Scholar Express Journal, 2023)
The article is devoted to the problems of dealing with realia in literary translation. Realia in literary translation refers to cultural and context-specific elements that are unique to a particular language or culture. These elements include objects, customs, traditions, social practices, and other aspects of everyday life that may be unfamiliar or unfamiliarly named in the target language or culture. Realia often pose challenges for translators because they require careful consideration to accurately convey the intended meaning and cultural nuances of the source text to the target audience.
Keywords: Accuracy; comprehension; challenges; adaptation